ANALYSIS OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE IN PROMOTING NURSING INNOVATION THROUGH KNOWLEDGE SHARING: A QUALITATIVE STUDY IN THE MAKKAH HEALTH CLUSTER, SAUDI ARABIA - Khadija Lafi Aljarary; Hafizah Che Hasan (PT. Jurnal Center Indonesia Publisher, 2026)
Transformational leadership and organizational culture are key determinants of nursing innovation in complex healthcare systems. However, limited qualitative evidence exists regarding how these factors interact with knowledge-sharing practices to foster innovation, particularly within healthcare organizations undergoing transformation in Saudi Arabia. This study aims to explore how transformational leadership and organizational culture influence nursing innovation through knowledge-sharing practices in the Makkah Health Cluster, Saudi Arabia. A qualitative exploratory design was conducted within six hospitals in the Makkah Health Cluster. The study included King Abdullah Medical City, Noor Specialist Hospital, Maternity and Child Hospital, King Abdulaziz Hospital, Hiraa General Hospital, and King Faisal Hospital. A total of 48 participants, including nursing managers, ICU head nurses, and clinical nurses with at least two years of experience, were selected using purposive sampling until data saturation was reached. Data were collected between January and March 2026 through semi-structured interviews, focus group discussions (FGDs), non-participant observations, and document analysis. All interviews and FGDs were audio-recorded, transcribed verbatim, and conducted in English or Arabic based on participant preference. Data were analyzed using Braun and Clarke’s thematic analysis approach, and study rigor was ensured through triangulation, member checking, and audit trail procedures following COREQ guidelines. Four key themes emerged: (1) transformational leadership as a catalyst for psychological safety and innovation engagement, (2) organizational culture characterized by a dual structure of collaboration and hierarchy, (3) knowledge sharing as a mechanism for collective clinical learning and problem-solving, and (4) nursing innovation as an emergent, practice-based, and collaborative process. Findings indicate that transformational leadership enhances nurses’ motivation and openness to innovation, while organizational culture shapes the environment for collaboration. Knowledge sharing functions as a critical process that transforms clinical experience into practical innovation in nursing care. Nursing innovation in the Makkah Health Cluster is a socially constructed and dynamic process shaped by the interaction of transformational leadership, organizational culture, and knowledge-sharing practices. Strengthening leadership capacity, fostering collaborative organizational culture, and developing structured knowledge management systems are essential to sustain nursing innovation and improve healthcare service quality.